2020
DOI: 10.1038/s41467-020-16835-z
|View full text |Cite
|
Sign up to set email alerts
|

Formation of ammonia–helium compounds at high pressure

Abstract: Uranus and Neptune are generally assumed to have helium only in their gaseous atmospheres. Here, we report the possibility of helium being fixed in the upper mantles of these planets in the form of NH 3-He compounds. Structure predictions reveal two energetically stable NH 3-He compounds with stoichiometries (NH 3) 2 He and NH 3 He at high pressures. At low temperatures, (NH 3) 2 He is ionic with NH 3 molecules partially dissociating into (NH 2) − and (NH 4) + ions. Simulations show that (NH 3) 2 He transforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 61 publications
(70 reference statements)
2
27
0
Order By: Relevance
“…The He atom essentially exhibits a spherical ELF distribution (Figure S7a) and there are no local ELF maxima along the directions He–Fe, He–O, and He–S, ruling out covalent interactions between He and other species. We examine the charge transfer based on Bader's topological analysis of the electron density (Bader, 1985). Bader charge analysis suggests a negligible charge transfer from the metallic aggregates to the He atom (Fe 50 : 0.13 e − ; Fe 40 O 10 : 0.09 e − ; and Fe 45 S 5 : 0.13 e − ) (Table S3), comparable to those in Na 2 He (Dong et al., 2017), FeO 2 He (J. Zhang et al., 2018), MgF 2 He (Z. Liu et al., 2018), NH 3 –He (Shi et al., 2020), H 2 O–He (H. Liu et al., 2015), and HeN 4 (Li et al., 2018) where the He atom does not form any local chemical bonds (i.e., keeps its inertness) but rather is located between like‐charged ions to shield their repulsive Coulomb interactions. We compute the projected electronic density of states (pDOS) to confirm the inertness of He in these metallic phases. We compare the two pDOSs for each phase with and without the He atom (Figure S7b).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The He atom essentially exhibits a spherical ELF distribution (Figure S7a) and there are no local ELF maxima along the directions He–Fe, He–O, and He–S, ruling out covalent interactions between He and other species. We examine the charge transfer based on Bader's topological analysis of the electron density (Bader, 1985). Bader charge analysis suggests a negligible charge transfer from the metallic aggregates to the He atom (Fe 50 : 0.13 e − ; Fe 40 O 10 : 0.09 e − ; and Fe 45 S 5 : 0.13 e − ) (Table S3), comparable to those in Na 2 He (Dong et al., 2017), FeO 2 He (J. Zhang et al., 2018), MgF 2 He (Z. Liu et al., 2018), NH 3 –He (Shi et al., 2020), H 2 O–He (H. Liu et al., 2015), and HeN 4 (Li et al., 2018) where the He atom does not form any local chemical bonds (i.e., keeps its inertness) but rather is located between like‐charged ions to shield their repulsive Coulomb interactions. We compute the projected electronic density of states (pDOS) to confirm the inertness of He in these metallic phases. We compare the two pDOSs for each phase with and without the He atom (Figure S7b).…”
Section: Resultssupporting
confidence: 63%
“…Zhang et al, 2018), MgF 2 He (Z. Liu et al, 2018), NH 3 -He (Shi et al, 2020), H 2 O-He (H. Liu et al, 2015), and HeN 4 (Li et al, 2018) where the He atom does not form any local chemical bonds (i.e., keeps its inertness) but rather is located between like-charged ions to shield their repulsive Coulomb interactions. (iii) We compute the projected electronic density of states (pDOS) to confirm the inertness of He in these metallic phases.…”
Section: Reactivity Of He In Metallic Meltsmentioning
confidence: 99%
“…These compounds are therefore essential to the understanding of the interior structure of planets. 4,[170][171][172][173][174][175][176][177] Here, we summarize the theory-guided synthesis of noble gas compounds, paying particular attention to Xe and He compounds (Table 4). 8a and b).…”
Section: Inorganic Electridesmentioning
confidence: 99%
“…Recent theoretical works have explored possible stable compounds formed by helium and the interior components of ice giants (e.g., CH 4 , NH 3 , and H 2 O). CSP methods have predicted many such compounds at high pressure and temperature conditions corresponding to those in planet interiors, such as He(NH 3 ) 2 , 172 He(H 2 O) 2 , 173,174 a superionic characteristic. Although these predicted compounds have yet to be conrmed, these theoretical results might be helpful for the understanding of the planet interior models and planets' evolution.…”
Section: Inorganic Electridesmentioning
confidence: 99%
“…Ice giants are mainly composed of H 2 O, NH 3 , and CH 4 ; their atmospheres are rich in He [21,25]. Theoretical studies have shown that H 2 O [26][27][28], NH 3 [28][29][30], and CH 4 [31] can form stable compounds with He at high pressure, and firstprinciples molecular dynamics suggests that both H 2 O-He and NH 3 -He may exist in a superionic state in the interiors of icy planets, in addition to the plastic state of NH 3 -He and the plastic or partially diffusive state of CH 4 -He at lower pressures and temperatures. Theoritical study reported that He can form stable crystalline compounds with iron at terapascal pressures [32].…”
mentioning
confidence: 99%